Effects of bio-nano-selenium on wheat grain morphology, selenium transport enrichment and antioxidant enzyme activities - Huang, Sisi; Han, Yali; Song, Ruilian; Wang, Xiaofang; Zhou, Yu; Luo, Hongmei; Ren, Xifeng; Yu, Kan (Frontiers in Plant Science, 2025)
Selenium (Se) is an essential trace element for human health, but selenium deficiency is widespread worldwide. In this study, we investigated the effects of selenium uptake, grain morphology, and antioxidant enzyme activities in three wheat varieties, including Huamai 1168 (high gluten), Huamai 2152 (medium gluten), and Wanximai 0638 (low gluten), by foliar spraying of bio-nano-selenium at the early flowering stage of wheat. The bio-nano-selenium nutrient solution was a patented product of microbial fermentation (Patent No. 201610338121.6) independently developed by our team, with a pure selenium concentration of 5000 mg/kg. The results showed that the total selenium content in all the varieties increased by 1843.52%, and the organic selenium content increased by 2009.87%, with Huamai 1168 showing the highest total selenium and organic selenium content. After selenium treatment, CAT activity decreased in all varieties; POD and SOD activities showed a tendency to increase and then decrease; MDA and proline content increased; and GSH content fluctuated during the filling period. Overall, foliar spraying of selenium enhanced antioxidant enzyme activities and improved the plants’ ability to cope with environmental stresses. In terms of agronomic traits, bio-nano-selenium positively affected plant height (12.63% increase on average), effective spike number (17.24% increase on average), and spikelet number (17.81% increase on average), but had a limited effect on grain morphology. In addition, bio-nano-selenium not only increased soil nutrient content but also promoted the uptake of hydrolyzed nitrogen, effective phosphorus, fast-acting potassium, and sulfate in wheat. In summary, bio-nano-selenium is expected to be an effective tool for selenium biofortification of wheat, which not only significantly increases the selenium content of grains but also improves yields, stress tolerance, and fertilizer utilization, providing a potential solution to selenium deficiency through dietary solutions, while contributing to the sustainable development of agriculture.